Assessment of leaching behavior of laterite soil amended with magnesium rich synthetic gypsum (MRSG) - Amira Ainna, Alias (2019)
The leachability and potential environmental risks of rare earth element (REE) and heavy metal in aquifer sediments from the recent industrial by-product waste of Lynas Advanced Materials Plan (LAMP), Gebeng, Pahang, Water Leached Purification (WLP) residue and Neutralization Underflow (NUF) residue as known as Magnesium Rich Synthetic Gypsum (MRSG) were investigated as assessment of leaching behavior. The main purpose of this study is to determine the leaching characteristic of laterite soil and MRSG amended soil under column test and oedometer test and comparing elements concentration with Toxicity Characteristic Leaching Procedure (TCLP) and National Drinking Water Quality Standard (NDWQS). The demand for MRSG is highly increased for land application purposes. Excessive usage of this materials on land may cause metal mobilization from the waste and subsequently infiltrated and polluted groundwater. Leaching of contaminated liquid containing high concentrations of heavy metals release from underlying groundwater will causing serious environmental damage. Leaching test are commonly used to assess the leaching potential of toxic substances and understand leaching behavior. Tests were carried out to analyse the element concentration using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Experimental result demonstrated that magnesium concentration increased when laterite was mixed with WLP and NUF, followed by 524.9 mg/l for 1:2:7, 911.9 mg/l for 1:3:6 mixture under 6.2 kPa while under 1589.8 kPa concentration increased by 508.3 mg/l to 1011 mg/l, respectively. The result recorded element concentration in oedometer leaching test were greater compared to columns leaching test. Overall, all element of concentration of contaminants were below the guideline of TCLP limit. However, element concentration of magnesium, aluminium, chromium and nickel were found exceed the limits set by NDWQS.